Fear in animals: a meta-analysis and review of risk assessment - Stankowich, Theodore (The Royal Society, 2005)
The amount of risk animals perceive in a given circumstance (i.e. their degree of ‘fear’) is a difficult motivational state to study. While many studies have used flight initiation distance as a proxy for fearfulness and examined the factors influencing the decision to flee, there is no general understanding of the relative importance of these factors. By identifying factors with large effect sizes, we can determine whether anti-predator strategies reduce fear, and we gain a unique perspective on the coevolution of predator and anti-predator behaviour. Based on an extensive review and formal meta-analysis, we found that predator traits that were associated with greater risk (speed, size, directness of approach), increased prey distance to refuge and experience with predators consistently amplified the perception of risk (in terms of flight initiation distance). While fish tolerated closer approach when in larger schools, other taxa had greater flight initiation distances when in larger groups. The presence of armoured and cryptic morphologies decreased perception of risk, but body temperature in lizards had no robust effect on flight initiation distance. We find that selection generally acts on prey to be sensitive to predator behaviour, as well as on prey to modify their behaviour and morphology.